Investigation of the arrangement of aluminum fins on the thermal behavior of lauric acid as a phase change material in a two-pipe heat exchanger by CFD simulation - Weidong Liu; Majid Mokhtari; Muntadher Abed Hussein; Anjan Kumar; Talib M. Albayati; Pardeep Singh Bains; Hadeel Kareem Abdul-Redha; Soheil Salahshour; M. Hekmatifar (Case Studies in Thermal Engineering)
Background: Phase change material (PCM) thermal storage systems store more thermal energy per unit volume than sensible heat storage systems. PCMs offer a potential solution to reduce energy consumption in various thermal engineering applications. This study aimed to examine how fin arrangement affected the thermal efficiency and melting time of PCMs. Methods: A two-dimensional numerical analysis of the melting process of lauric acid in a heat exchanger featuring two pipelines and fins was conducted using CFD simulation. In most previous investigations, the heat transfer fluid was a single-phase liquid. An enthalpy-porosity technique was used to model the solid and liquid phases of PCM. The governing equations were solved using the commercial software ANSYS Fluent 2021, and the pressure and velocity equations were coupled using the SIMPLE algorithm. Significant findings: The best model among the 13 tested was Model 5, which featured 6 fins and a consistent angle of 60°. For Model 5, the melting time was 1818.3 s. Due to sensible heating, the fin's temperature (Temp) rose gradually from 300 K to 318 K. Temp then gradually increased as the PCM melted in the phase transition zone between 316.5 K and 321.2 K. Once the phase transition was complete, the PCM's Temp steadily rose from 324 K to 340 K. In Model 5, the inner wall Temp and the maximum Temp of the PCM were closest, at 327.34 K and 333.55 K, respectively. The thermal shock between the PCM and the ambient Temp caused a peak heat flux at the beginning of the PCM loading process.